Are European part-time MBA programs designed to foster entrepreneurial minds? An exploratory study - Montserrat Entrialgo; Víctor Iglesias; Frank Müller (Administrative Sciences, 2019)
Are the MBA programs really designed to foster entrepreneurial minds? Answering this question is the main objective of our work. After a literature review we identified several programs' characteristics that promote entrepreneurship. Using a sample of 99 executive or part-time MBA programs, we found that the diversity in this sector is high. Not all the programs have been designed to foster entrepreneurship behavior;moreover,most of themdo not even have an entrepreneurship subject in their curriculum. Nevertheless, other dimensions that favor this type of behavior, like internationality, are widespread in the European MBA market.
Keywords: 350; MBA; entrepreneurship education; internationality; higher education